Marriage and Consumption Insurance: What’s Love Got to Do with It? - Hess, Gregory D. (Journal of Political Economy, 2004)
When markets are incomplete, individuals may choose to marry to diversify their labor income risk. Love, however, can complicate the picture. If love is fleeting or the resolution of agents’ income uncertainty occurs predominantly later in life, then marriages with good economic matches last longer. In contrast, if love is persistent and the resolution of uncertainty to agents’ income occurs early, then marriages with good economic matches are more likely to be caught short with too little love to save a marriage. Consequently, once married, the partners will be more likely to divorce. Evidence is provided to distinguish between these alternative scenarios.